MEMBANGUN BANGSA INDONESIA DENGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Andang Sunarto (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The rapid  development of information and  communication technology (read: ICT) has  changed the procedure for humans act and behave today, as well as college graduates as an elite human capital, particularly in relation  to the  process of communication and  interaction. It is a fact that  almost  all industrial  fields and aspects of modern life do not escape the reach of this technology, because it has been proven to be able to bring a number of value and benefit  to the national  development significant Indonesia and civilization of mankind in this world. With the advancement in the field of ICT is growing at an exponentially and take the positives out of the field of ICT is expected to be Indonesian nation to excel in all areas.